The Normality Criteria of Meromorphic Functions Concerning Shared Fixed-Points - Wei Chen; Qi Yang; Wen-jun Yuan; Hong-gen Tian (Discrete Dynamics in Nature and Society)
We study the normality criteria of meromorphic functions concerning shared fixed-points; we obtain the following: Let ℱ be a family of meromorphic functions defined in a domain D and k≥2 a positive integer. For every f∈ℱ, all zeros of f are of multiplicity at least k+2 and all poles of f are multiple. If ff(k) and gg(k) share z in D for each pair of functions f and g, then ℱ is normal.